Extending the utility of treemaps with flexible hierarchy - Chintalapani, Gouthami; Plaisant, Catherine; Shneiderman, Ben (IV'04: Proceedings of the International Conference on Information Visualisation, 2004)
Treemaps are a visualization technique for presenting hierarchical information on two-dimensional displays. Prior implementations limit the visualization to pre-defined static hierarchies. Flexible hierarchy, a new capability of Treemap 4.0, enables users to define various hierarchies through dynamically selecting a series of data attributes so that they can discover patterns, clusters and outliers. This work describes the design and implementation issues of flexible hierarchy. It then reports on a usability study, which led to enhancements to the interface.